Peculiarities of manifestation of cognitive-stylistic characteristics and creativity of public servants - Fedotova , Tetiana; Kulchytska , Anna (Psychological Prospects Journal, 2020)
Purpose. The article is devoted to the peculiarities of cognitive-stylistic characteristics and creativity of public servants. Within the consideration of this topic, a detailed theoretical and methodological analysis and systematization of approaches in the study of the concept of cognitive style and creativity of the individual was made, as well as an empirical study of cognitive-stylistic characteristics and creativity of public servants with different professional experience. Cognitive style in this study is considered as an individual difference in the processes of information processing and determining the characteristics of the organization of the cognitive sphere of personality. Creativity is defined as a personal characteristic that manifests itself in the ability to generate unusual ideas, deviate from traditional patterns of thinking, quickly solve problem situations, and so on.Methods. To achieve the purpose of the study, we used the following methods: theoretical; organizational; empirical (complex of psychodiagnostic methods), namely "Verbal Labyrinth", "Figures of Gottschaldt", the method of figured form A of the test of creative thinking E.P. Torrens (adapted by O. Tunic), the questionnaire of J. Johnson (adapted by O. Tunic).Results. In the empirical part of the study, the authors identified differences in cognitive-stylistic characteristics and creativity in public servants with different professional experience: with experience of 6-10 years – a high level of creativity, independence and flexibility; with 11-20 years of experience – a moderate level of creativity, independence and rigidity of thinking; with more than 20 years of experience – field dependence and rigidity of thinking. In all selected groups, there were statistically significant direct links between creativity and field independence and flexibility of thinking, speed of task completion and development, as well as the relationship between creativity and professional experience.Conclusions. The results of the empirical study can be used in the development of a series of professional programs to improve the skills of public servants, including the formation of their professional competencies.
Keywords: cognitive style; cognitive control; cognitive processes; creativity; originality; flexibility